Webgis Fasilitas Kesehatan di Kabupaten Demak dengan Leaflet dan Web Mapping Interaktif Client-Side - Muhammad Rizal Wahyu Aji Saputra; Theresia Dwiati Wismarini (Sekawan Institut, 2025)
Geographic Information Systems (GIS) have become an essential tool in the planning and management of various sectors, including the health sector. This research aims to create an interactive WebGIS focused on mapping healthcare service locations in Demak Regency. Using the Leaflet JavaScript framework, this ap-plication is built with a client-side application approach, allowing data processing and map display to be performed directly in the user's browser. The interactive web mapping method is applied to provide a more lively user experience, where users can easily search, filter, and obtain detailed information about hospitals, community health centers, clinics, and other healthcare facilities in the Demak area. Geographic data and attributes from healthcare facilities are collected and combined into the system for precise visualization. The result of this development is a responsive, easily accessible web application that provides appropriate spatial information for the community, local government, and related parties to support decision-making regarding access to and distribution of healthcare services in Demak Regency. This system is expected to improve efficiency in identifying and utilizing existing healthcare facilities.